Pengujian Undang-Undang Oleh Mahkamah Konstitusi Dalam Rangka Kontrol Terhadap Kekuatan Politik Dewan Perwakilan Rakyat - Irman, Irman (Jurnal Selat, 2013)
Power to make laws in Indonesia are in the House of Representatives, where the Parliament is a representative or representatives of the people to represent the interests of all the people in civic life. In the process of law making is affected by the interests of a handful of elite and clas sso that the pureform of law that has the purpose of public interest is always neglected. with the Constitutional Court has judicial authority both material and formale ffort stoprovidea control or control of political interests that are not based on common nterests.  Keyword: Legislation and control